(untitled) (Ius Novum, 2025)
The article analyses a new regulation in Polish criminal procedure. The Act of 14 April 2023, amending the Code of Criminal Procedure introduced a new right for the suspect, i.e. the possibility of the presence of a legal representative, actual guardian, or a person indicated by a minor suspect during a procedural act in preparatory proceedings involving the suspect. That person shall have the status of a third party who, although not usually a party to the proceedings, functions as a special person of trust. Despite some reservations concerning certain elements of this regulation, it deserves appreciation, as it is aimed at strengthening the protection of the suspect’s interests and guaranteeing the proper conduct of procedural acts.